STUDI TENTANG PENGARUH PERSEPSI MANFAAT DAN PERSEPSI RESIKO TERHADAP SIKAP PADA BELANJA ONLINE DAN IMPLIKASINYA PADA MINAT BELANJA ONLINE DI D’SHETWO BOUTIQUE - Triwidyastika, Ardinia (Master of Management Diponegoro University, 2012)
Online buying becoming a trend for people in this digital era. This is due to internet facilities is widely used by many people in Indonesia. It is very convenience shopping using online system. However, customers are remain in doubt for the risks incurred by online buying.The study is attempted to analyze the influence of words of mouth, perceived of convenience transaction, experience in online shopping, risks and benefit perceived, and attitude towards the intention of online buying of respondents in the study area. Respondents were selected from the potential buyers of D’Shetwo Boutique in Semarang. There 167 respondents were given questionnaire. The estimation technique of Structural Equation Model (SEM) with seven variables was invoked to prove the hypothesis.The result found that the hypothesis of more easier transaction can be done then, will more less risk to proceed the online shopping. However, this hypothesis was failed to be proved in this study. This implies that an easy transaction may not able to induce the intention of buying online. Therefore, this study suggested that an experience in online buying is really efficient to alleviate its risks by promoting positive attitude in online shopping will encourage the intention to buy online for the potential customers.